The recognition of a period of studies abroad as a determinant for learning mobility of female students of pedagogy - Mateusz Marciniak (Maria Curie-Skłodowska University, Lublin, Poland, 2021)
Introduction: The implementation of the Bologna Process has contributed to the rising level of recognition of qualifications and study periods in higher education. Consequently, the level of student mobility increased (e.g. Erasmus+). Current research shows, that the recognition of courses completed abroad is important, yet not crucial factor that impacts mobility. Research Aim: The research aim is to determine the attitudes of university students towards the recognisability of study period abroad as challenge linked to mobility. Method: The study was carried out in 2017-2019 at the Faculty of Educational Studies of Adam Mickiewicz University (AMU) in Poznan, Poland. The research sample were female students of pedagogy recruited to the Erasmus+ programme (N=50) and those not planning to participate in it (N=64). The study was conducted in the diagnostic-dependence model (auditorium survey method with questionnaire). Results: Relatively more female students of pedagogy perceived the similarity between subjects at partner universities and AMU as a source of potential advantage (86%) rather than inconvenience of participating in Erasmus+ (57%). Individual completion of curriculum differences was identified as opportunity (78%) rather than threat (57%). The level of recognisability by home university was described as opportunity (70%) as frequently as inconvenience (71%). Considerably more students who did not plan mobility (compared to those recruited) indicated potential inconveniences within analysed factors. Conclusion: For internationalisation strategies within "rebuilding" student mobility after COVID-19 pandemic, it may be important to intensify activities aimed at minimizing fears and inconveniences related to the recognition of courses completed during exchange.